PENGARUH CURRENT RATIO, CASH RATIO, DEBT TO EQUITY RATIO DAN NET PROFIT MARGIN TERHADAP KINERJA KEUANGAN PERUSAHAAN SEKTOR KESEHATAN DI BEI - Amalia, Ina; Astuti, Puji; Faisol, Faisol (UNIKA Santo Thomas, 2024)
This research is motivated by the fact that the level of net profit of health sector manufacturing companies fluctuates from year to year. This situation indicates that the company's financial performance is inconsistent. Therefore, the aim of the research is to determine the influence of the Current Ratio, Cash Ratio, Debt to Equity Ratio and Net Profit Margin on Performance. Finance. This research uses a causal quantitative approach. The data used is secondary data in the form of financial reports of health sector manufacturing companies listed on the IDX. The sample used was 13 health companies using purposive sampling technique, there were 52 observation units. The data analysis technique uses panel data regression analysis with STATA 17 software, classic assumption tests with multicollinearity tests, heteroscedasticity tests and normality tests. Hypothesis testing was carried out using the t test (Partial) and F test (Simultaneous) with results showing that the Current Ratio, Debt to Equity Ratio and Net Profit Margin partially influenced Financial Performance (ROA), while the Cash Ratio partially had no influence on Performance. Finance (ROA). Simultaneously Current Ratio, Cash Ratio, Debt to Equity Ratio and Net Profit Margin influences Financial Performance (ROA). Companies are expected to be able to optimize the turnover of cash and cash equivalents so that they can produce and increase optimal net profit.